Changes in Relative Female-Male Unemployment : a Canadian-United States Comparison - Della Valle, P.; Meyer, B. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This paper seeks to examine the impact of the level of cyclical economic activity and of the relative female-male participation rates on the structure of the relative unemployment rates of women and men.